Counterterrorism : ASEAN Militaries’ Growing Role - Gunaratna, Rohan (2018)
Following its defeat in Iraq and Syria last year the self-proclaimed Islamic State (IS) has expanded to other parts of the Muslim world including Southeast Asia by linking up with local militant groups. Countries in the region recognise the need for stronger cooperation in counter-terrorism and are increasingly roping in their militaries.